Construing Structure in Engineering Texts in the Framework of SFL - Mulyati Khorina; Saudin; Danny Nugraha (Jurnal Bahasa Inggris Terapan, 2022)
This paper deals with how a structure is construed in engineering texts. Hence, the purpose of this study is to investigate the realization of structure viewed from Systemic Functional Linguistics (SFL). The method used in this study was a qualitative one. The data were obtained from two engineering textbooks functioning as references. Analyzing the data by applying SFL reveals that the structure is construed by relational process clauses, especially circumstantial relational clauses. The relational process belongs to attributive ones realized by various lexical verbs: support, assemble, attach, fasten, and bolt. Whereas, the circumstantial elements which represent Attribute semantically serves as Means and Place.